Gut microbiota derived DCA enhances FOLFOX efficacy via Ugt1a6b mediated enterohepatic circulation in colon cancer - Qian Fang; Xiaoying Hou; Limei Fan; Yufei Deng; Xiaoxuan Li; Hongyun Zhang; Haiping Wang; Zhengqi Fu; Binlian Sun; Xiji Shu; Hongzhi Du; Yuchen Liu (Pharmacological Research)
FOLFOX (5-Fluorouracil, Calcium Folinate combined with Oxaliplatin) is a preferred chemotherapy regimen for colon cancer, but its limited efficacy remains a major challenge, significantly impairs patient outcomes. There is an urgent need to identify strategies to improve its therapeutic effectiveness. Our previous studies have suggested that gut microbiota-derived bile acids may be involved in the anticancer effect of FOLFOX in vitro, however, the underlying mechanism remains unclear. In this study, we investigated the role of bile acids in modulating FOLFOX efficacy and the related mechanisms. We first demonstrated that bile acids depletion (cholestyramine treatment) enhanced FOLFOX efficacy in an orthotopic colon cancer mouse model, suggesting that bile acids play a key role in FOLFOX’s therapeutic effects. Further, based on the system screen of 15 bile acids on FOLFOX efficacy via MTT, colony formation and flow cytometry assay, Deoxycholic Acid (DCA) and Glycodeoxycholic Acid (GDCA) were annotated as potential modulators of FOLFOX efficacy. Among these, DCA was further validated to significantly enhance FOLFOX’s anti-colon cancer effects in vivo. Transcriptomic analysis and subsequent biological experiments revealed that DCA enhanced FOLFOX efficacy via Ugt1a6b. In conclusion, our findings establish that gut microbiota-derived DCA enhances the efficacy of FOLFOX potentially via Ugt1a6b mediated enterohepatic circulation, providing novel insights into a synergistic therapeutic strategy for improving colon cancer treatment.